Desenvolvimento e caracterização de filmes biodegradáveis de blendas de TPS/PVOH reforçados com derivados de arroz - Emanuelle, Delgado (Universidade Federal de São Carlos, 2025)
Synthetic polymeric materials derived from non-renewable sources have a significant environmental impact, highlighting the need for sustainable alternatives. Thermoplastic starch (TPS), derived from renewable sources, appears to be a promising option; however, its mechanical and moisture barrier properties have limitations. To overcome these limitations and optimize the properties of starch films, plasticizers and organic reinforcing agents, such as those derived from rice, can be added. These materials are silica-rich industrial waste generated during the rice processing process and have shown great potential for improving the properties of composites. Therefore, this work investigates the extrusion and characterization of biodegradable films made from TPS/PVOH blends reinforced with rice byproducts such as rice hulls (RH) and carbonized rice hulls (CHR). For this purpose, a TPS/PVOH blend plasticized with glycerol was produced, incorporating different mass contents of CA and CCA (5%, 10%, and 20%) as reinforcing agents. The films were obtained by extrusion and characterized by DSC, TGA, SEM, FTIR, and tensile testing, in addition to water absorption and solubility analyses. The composites with 10% CA and 10% CCA showed lower water absorption, indicating greater moisture resistance, while formulations with 5% CA, 20% CA, and 5% CCA demonstrated greater absorption. Water degradation followed similar trends, with emphasis on the composites with 5% CA and 10% CA. Thermal analyses showed that increasing the filler had little influence on the crystallinity (DSC) and thermal stability (TGA) of the composites. FTIR indicated predominantly physical interactions between the matrix and filler. Mechanical tests revealed higher tensile strength for composites with 5% and 10% CA, a result corroborated by SEM analyses. The TPS/PVOH/10% CA formulation presented the best overall performance, with improved physical, thermal, and mechanical properties, demonstrating its potential as a sustainable alternative for partial replacement of conventional polymers.
Development and characterization of biodegradable films from TPS/PVOH blends reinforced with rice derivatives
Keywords: Amido termoplástico; Filmes biodegradáveis; Casca de arroz; Extrusão; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS